Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Experimental investigations of uniaxial and biaxial cold stretching within PC‐films and bars using optical measurements - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Polycarbonate (PC) is an amorphous polymer that is an extremely robust material with a high tenacity, and thus suitable for a lightweight construction with glass‐like transparency. Due to these advantageous properties, PC is often used in industry for example in medical devices, automotive headlamps, sporting equipment, electronics, and a variety of other products. PC is often subjected to uniaxial and biaxial loading conditions. Therefore, reliable material models have to take into account the various resulting experimental effects. For those reasons, we investigate PC specimens under uniaxial and biaxial loading by using different stretch rates and loading scenarios. In addition to that, we propose methods for optical measurement of local stretches to obtain the approximated local true stress. In future work, the displacement fields and the resulting reaction forces will be used for parameter identification of constitutive equations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Thermo‐chemo‐mechanical modelling of a curing process combined with mean‐field homogenization methods at large strains - Lenz, Peter; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A thermodynamic framework for the phase‐field approach considering carbide precipitation during phase transformations - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Definition of High-Risk Motion Patterns for Female ACL Injury Based on Football-Specific Field Data: A Wearable Sensors Plus Data Mining Approach - Di Paolo, Stefano; Nijmeijer, Eline M.; Bragonzoni, Laura; Gokeler, Alli; Benjaminse, Anne (Sensors)
The aim of the present study was to investigate if the presence of anterior cruciate ligament (ACL) injury risk factors depicted in the laboratory would reflect at-risk patterns in football-specific field data. Twenty-four female footballers (14.9 ± 0.9 year) performed unanticipated cutting maneuvers in a laboratory setting and on the football pitch during football-specific exercises (F-EX) and games (F-GAME). Knee joint moments were collected in the laboratory and grouped using hierarchical agglomerative clustering. The clusters were used to investigate the kinematics collected on field through wearable sensors. Three clusters emerged: Cluster 1 presented the lowest knee moments; Cluster 2 presented high knee extension but low knee abduction and rotation moments; Cluster 3 presented the highest knee abduction, extension, and external rotation moments. In F-EX, greater knee abduction angles were found in Cluster 2 and 3 compared to Cluster 1 (p = 0.007). Cluster 2 showed the lowest knee and hip flexion angles (p < 0.013). Cluster 3 showed the greatest hip external rotation angles (p = 0.006). In F-GAME, Cluster 3 presented the greatest knee external rotation and lowest knee flexion angles (p = 0.003). Clinically relevant differences towards ACL injury identified in the laboratory reflected at-risk patterns only in part when cutting on the field: in the field, low-risk players exhibited similar kinematic patterns as the high-risk players. Therefore, in-lab injury risk screening may lack ecological validity.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Goal‐oriented adaptivity based on a model hierarchy of mean‐field and full‐field homogenization methods in elasto‐plasticity - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Demonstration of Hong-Ou-Mandel interference in an LNOI directional coupler - Babel, Silia; Bollmers, Laura; Massaro, Marcello; Luo, Kai Hong; Stefszky, Michael; Pegoraro, Federico; Held, Philip; Herrmann, Harald; Eigner, Christof; Brecht, Benjamin; Padberg, Laura; Silberhorn, Christine (Optics Express)
Interference between single photons is key for many quantum optics experiments and applications in quantum technologies, such as quantum communication or computation. It is advantageous to operate the systems at telecommunication wavelengths and to integrate the setups for these applications in order to improve stability, compactness and scalability. A new promising material platform for integrated quantum optics is lithium niobate on insulator (LNOI). Here, we realise Hong-Ou-Mandel (HOM) interference between telecom photons from an engineered parametric down-conversion source in an LNOI directional coupler. The coupler has been designed and fabricated in house and provides close to perfect balanced beam splitting. We obtain a raw HOM visibility of (93.5 ± 0.7) %, limited mainly by the source performance and in good agreement with off-chip measurements. This lays the foundation for more sophisticated quantum experiments in LNOI.
Keywords: Atomic and Molecular Physics; and Optics

Home-Based Measurements of Nocturnal Cardiac Parasympathetic Activity in Athletes during Return to Sport after Sport-Related Concussion - Delling, Anne Carina; Jakobsmeyer, Rasmus; Coenen, Jessica; Christiansen, Nele; Reinsberger, Claus (Sensors)
Sport-related concussions (SRC) are characterized by impaired autonomic control. Heart rate variability (HRV) offers easily obtainable diagnostic approaches to SRC-associated dysautonomia, but studies investigating HRV during sleep, a crucial time for post-traumatic cerebral regeneration, are relatively sparse. The aim of this study was to assess nocturnal HRV in athletes during their return to sports (RTS) after SRC in their home environment using wireless wrist sensors (E4, Empatica, Milan, Italy) and to explore possible relations with clinical concussion-associated sleep symptoms. Eighteen SRC athletes wore a wrist sensor obtaining photoplethysmographic data at night during RTS as well as one night after full clinical recovery post RTS (>3 weeks). Nocturnal heart rate and parasympathetic activity of HRV (RMSSD) were calculated and compared using the Mann–Whitney U Test to values of eighteen; matched by sex, age, sport, and expertise, control athletes underwent the identical protocol. During RTS, nocturnal RMSSD of SRC athletes (Mdn = 77.74 ms) showed a trend compared to controls (Mdn = 95.68 ms, p = 0.021, r = −0.382, p adjusted using false discovery rate = 0.126) and positively correlated to “drowsiness” (r = 0.523, p = 0.023, p adjusted = 0.046). Post RTS, no differences in RMSSD between groups were detected. The presented findings in nocturnal cardiac parasympathetic activity during nights of RTS in SRC athletes might be a result of concussion, although its relation to recovery still needs to be elucidated. Utilization of wireless sensors and wearable technologies in home-based settings offer a possibility to obtain helpful objective data in the management of SRC.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Fully guided and phase locked Ti:PPLN waveguide squeezing for applications in quantum sensing - Domeneguetti, Renato; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas S.; Gehring, Tobias (Optics Letters)
This work reports a fully guided setup for single-mode squeezing on integrated titanium-indiffused periodically poled nonlinear resonators. A continuous-wave laser beam is delivered and the squeezed field is collected by single-mode fibers; up to −3.17(9) dB of useful squeezing is available in fibers. To showcase the usefulness of such a fiber-coupled device, we applied the generated squeezed light in a fiber-based phase sensing experiment, showing a quantum enhancement in the signal-to-noise ratio of 0.35 dB. Moreover, our investigation of the effect of photorefraction on the cavity resonance condition suggests that it causes system instabilities at high powers.
Keywords: Atomic and Molecular Physics; and Optics

UV-enhanced environmental charge compensation in near ambient pressure XPS - Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

Transferability of a discrepancy model for the dynamics of electromagnetic oscillating circuits - Wohlleben, Meike Claudia; Muth, Lars; Peitz, Sebastian; Sextro, Walter (Proceedings in Applied Mathematics and Mechanics)
Modelling of dynamic systems plays an important role in many engineering disciplines. Two different approaches are physical modelling and data‐driven modelling, both of which have their respective advantages and disadvantages. By combining these two approaches, hybrid models can be created in which the respective disadvantages are mitigated, with discrepancy models being a particular subclass. Here, the basic system behaviour is described physically, that is, in the form of differential equations. Inaccuracies resulting from insufficient modelling or numerics lead to a discrepancy between the measurements and the model, which can be compensated by a data‐driven error correction term. Since discrepancy methods still require a large amount of measurement data, this paper investigates the extent to which a single discrepancy model can be trained for a physical model with additional parameter dependencies without the need for retraining. As an example, a damped electromagnetic oscillating circuit is used. The physical model is realised by a differential equation describing the electric current, considering only inductance and capacitance; dissipation due to resistance is neglected. This creates a discrepancy between measurement and model, which is corrected by a data‐driven model. In the experiments, the inductance and the capacity are varied. It is found that the same data‐driven model can only be used if additional parametric dependencies in the data‐driven term are considered as well.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

Numerical investigations of new low‐order explicit last stage diagonal implicit Runge–Kutta schemes with the finite‐element method - Westermann, Hendrik; Mahnken, Rolf (PAMM)
Abstract Initial value problems can be solved efficiently by means of Runge–Kutta algorithms with adaptive step size control. Diagonally implicit Runge–Kutta (DIRK) methods are the most popular class among the diverse family of Runge–Kutta algorithms. In this paper, the novel class of low‐order explicit last‐stage diagonally implicit Runge–Kutta (ELDIRK) methods are explored, which combine implicit schemes with an additional explicit evaluation as an explicit last stage. ELDIRK Butcher tableaus are used to control embedded RK methods to obtain solutions of different orders. The lower‐order solution is obtained by classical implicit RK stages and the higher‐order solution is obtained by additional explicit evaluation. As a result, a significant reduction in computational cost is achieved by skipping the iterative solution of nonlinear systems for the additional step. The examination of the heat problem and the use of the innovative Butcher tableau in the finite‐element method are the main contributions of this work. Thus, it is possible to establish adaptive step size control for the new low‐order embedded methods based on an empirical method for error estimation. Two‐dimensional simulations are used to show an appropriate algorithm for the ELDIRK schemes. The new Runge–Kutta schemes' predictions of higher‐order convergence are confirmed, and their successful outcomes are illustrated.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics

Downwind and upwind approximations for mesh and model adaptivity of elasto‐plastic composites - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract The use of heterogeneous materials, such as composites with Prandtl‐Reuss‐type material laws, has increased in industrial praxis, making finite element modeling with homogenization techniques a well‐accepted tool. These methods are particularly advantageous to account for microstructural mechanisms which can be related to nonlinearities and time‐dependency due to elasto‐plasticity behavior. However, their advantages are diminished by increasing computational demand. The present contribution deals with the balance of accuracy and numerical efficiency of nonlinear homogenization associated with a framework of goal‐oriented adaptivity, which takes into account error accumulation over time. To this end, model adaptivity of homogenization methods is coupled to mesh adaptivity on the macro scale. Our new proposed adaptive procedure is driven by a goal‐oriented a posteriori error estimator based on duality techniques using downwind and upwind approximations. Due to nonlinearities and time‐dependency of the plasticity, the estimation of error transport and error generation is obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Finally, a numerical example illustrates the effectiveness of the proposed adaptive approach.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

A micropolar model accounting for asymmetric behavior of cold‐box sand in relation to tensile and compression tests - Börger, Alexander; Mahnken, Rolf (PAMM)
Abstract Cold‐box sand (CBS) belongs to the granular materials and consists of sand and a binder. The behavior of CBS is simulated with a micropolar model, whereby the additional degree of freedom of the model describes the rotation of the sand grains. The model is used to generate a shear band under pressure for three different meshes, where the force‐displacement curves of the three meshes converge so that no mesh dependence occurs. Another requirement of the model is the consideration of asymmetric behavior for compression and tension. Due to the additional degree of freedom the implicit implementation of the micropolar continuum is very time‐consuming. Therefore, an explicit implementation is considered as an alternative possibility. This paper compares the advantages and disadvantages of both methods and the results for both calculations.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

High‐Resolution X‐ray Absorption and Emission Spectroscopy for Detailed Analysis of New CO2 Methanation Catalysts - Strübbe, Sven; Nowakowski, Michał; Schoch, Roland; Bauer, Matthias (ChemPhysChem)
Abstract A new approach for the characterization of CO 2 methanation catalysts prepared by thermal decomposition of a nickel MOF by hard X‐ray photon‐in/photon‐out spectroscopy in form of high energy resolution fluorescence detected X‐ray absorption near edge structure spectroscopy (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is presented. In contrast to conventional X‐ray absorption spectroscopy, the increased resolution of both methods allows a more precise phase determination of the final catalyst, which is influenced by the conditions during MOF decomposition.
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Broadband Mie scattering effects by structural features of setae from the Saharan silver ant Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Journal of the Optical Society of America B)
The Saharan desert ant Cataglyphis bombycina is densely covered with shiny silver setae (hair-like structures). Their appearance was explained by geometric optics and total internal reflection. The setae also increase the emissivity of the ant, as they form an effective medium. This work provides additional data on microstructural details of the setae that are used to simulate the scattering of an individual seta to explain their influence on the optical properties. This is achieved by characterization of their structure using light microscopy and scanning/transmission electron microscopy. How the microstructural features influence scattering is investigated wave-optically within the limits of finite-difference time-domain simulations from the ultraviolet to the mid-infrared spectral range to elucidate the optical effects beyond ray optics and effective medium theory. The results show that Mie scattering plays an important role in protecting the ant from solar radiation and could be relevant for its thermal tolerance.
Keywords: Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics

Electric-field-induced second harmonic generation in silicon dioxide - Widhalm, Alex; Golla, Christian; Weber, Nils; Mackwitz, Peter; Zrenner, Artur; Meier, Cedrik (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Asymmetric parametric generation of images with nonlinear dielectric metasurfaces - Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Dong, Zhaogang; Yang, Joel; Zentgraf, Thomas; Kivshar, Yuri (Nature Photonics)
Subwavelength dielectric resonators assembled into metasurfaces have become a versatile tool for miniaturizing optical components approaching the nanoscale. An important class of metasurface functionalities is associated with asymmetry in both the generation and transmission of light with respect to reversals of the positions of emitters and receivers. The nonlinear light–matter interaction in metasurfaces offers a promising pathway towards miniaturization of the asymmetric control of light. Here we demonstrate asymmetric parametric generation of light in nonlinear metasurfaces. We assemble dissimilar nonlinear dielectric resonators into translucent metasurfaces that produce images in the visible spectral range on being illuminated by infrared radiation. By design, the metasurfaces produce different and completely independent images for the reversed direction of illumination, that is, when the positions of the infrared emitter and the visible light receiver are exchanged. Nonlinearity-enabled asymmetric control of light by subwavelength resonators paves the way towards novel nanophotonic components via dense integration of large quantities of nonlinear resonators into compact metasurface designs.
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Apparatus for the measurement of the thermodynamic speed of sound of diethylene glycol and triethylene glycol - Javed, Muhammad Ali; Vater, Sebastian; Baumhögger, Elmar; Windmann, Thorsten; Vrabec, Jadran (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Thermodynamic Properties for 1-Hexene – Measurements and Modeling - Betken, Benjamin; Beckmüller, Robin; Ali Javed, Muhammad; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Brillouin and Raman imaging of domain walls in periodically-poled 5%-MgO:LiNbO3 - Rix, Jan; Rüsing, Michael; Galli, Roberta; Golde, Jonas; Reitzig, Sven; Eng, Lukas M.; Koch, Edmund (Optics Express)
Recently, ferroelectric domain walls (DWs) have attracted considerable attention due to their intrinsic topological effects and their huge potential for optoelectronic applications. In contrast, many of the underlying physical properties and phenomena are not well characterized. In this regard, analyzing the vibrational properties, e.g. by Raman spectroscopy, provides direct access to the various local material properties, such as strains, defects or electric fields. While the optical phonon spectra of DWs have been widely investigated in the past, no reports on the acoustic phonon properties of DWs exist. In this work, we present a joint Raman and Brillouin visualization of ferroelectric DWs in the model ferroelectric lithium niobate. This is possible by using a combined Raman and virtually imaged phased array Brillouin setup. Here, we show that DWs can be visualized via frequency shifts observed in the acoustic phonons, as well. The observed contrast then is qualitatively explained by models adapted from Raman spectroscopy. This work, hence, provides a novel route to study ferroelectric DWs and their intrinsic mechanical properties.
Keywords: Atomic and Molecular Physics; and Optics

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Optical Arbitrary Waveform Measurement Using Silicon Photonic Slicing Filters - Fang, Dengyang; Zazzi, Andrea; Müller, Juliana; Dray, Daniel; Fullner, Christoph; Marin-Palomo, Pablo; Tabatabaei Mashayekh, Alireza; Dipta Das, Arka; Weizel, Maxim; Gudyriev, Sergiy; Freude, Wolfgang; Randel, Sebastian; et al. (Journal of Lightwave Technology)
We demonstrate an optical arbitrary waveform measurement (OAWM) system that exploits a bank of silicon photonic (SiP) frequency-tunable coupled-resonator optical waveguide (CROW) filters for gapless spectral slicing of broadband optical signals. The spectral slices are coherently detected using a frequency comb as a multi-wavelength local oscillator (LO) and stitched together by digital signal processing (DSP). For high-quality signal reconstruction, we have implemented a maximum-ratio combining (MRC) technique based on precise calibration of the complex-valued opto-electronic transfer functions of all detection paths. In a proof-of-concept experiment, we demonstrate the viability of the scheme by implementing a four-channel system that offers an overall detection bandwidth of 140 GHz. Exploiting a femtosecond laser with precisely known pulse shape for calibration along with dynamic amplitude and phase estimation, we reconstruct 100 GBd QPSK, 16QAM and 64QAM optical data signals. The reconstructed signals show improved quality compared to that obtained with a single high-speed intradyne receiver, while the electronic bandwidth requirements of the individual coherent receivers are greatly reduced.
Keywords: Atomic and Molecular Physics; and Optics

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Towards Quantum One-Time Memories from Stateless Hardware - Broadbent, Anne; Gharibian, Sevag; Zhou, Hong-Sheng (Quantum)
A central tenet of theoretical cryptography is the study of the minimal assumptions required to implement a given cryptographic primitive. One such primitive is the one-time memory (OTM), introduced by Goldwasser, Kalai, and Rothblum [CRYPTO 2008], which is a classical functionality modeled after a non-interactive 1-out-of-2 oblivious transfer, and which is complete for one-time classical and quantum programs. It is known that secure OTMs do not exist in the standard model in both the classical and quantum settings. Here, we propose a scheme for using quantum information, together with the assumption of stateless (i.e., reusable) hardware tokens, to build statistically secure OTMs. Via the semidefinite programming-based quantum games framework of Gutoski and Watrous [STOC 2007], we prove security for a malicious receiver making at most 0.114n adaptive queries to the token (for n the key size), in the quantum universal composability framework, but leave open the question of security against a polynomial amount of queries. Compared to alternative schemes derived from the literature on quantum money, our scheme is technologically simple since it is of the "prepare-and-measure" type. We also give two impossibility results showing certain assumptions in our scheme cannot be relaxed.
Keywords: Physics and Astronomy (miscellaneous); Atomic and Molecular Physics; and Optics

Bright correlated twin-beam generation and radiation shaping in high-gain parametric down-conversion with anisotropy - Riabinin, M.; Sharapova, Polina; Meier, Torsten (Optics Express)
Uniaxial anisotropy in nonlinear birefringent crystals limits the efficiency of nonlinear optical interactions and breaks the spatial symmetry of light generated in the parametric down-conversion (PDC) process. Therefore, this effect is usually undesirable and must be compensated for. However, high gain may be used to overcome the destructive role of anisotropy in order to generate bright two-mode correlated twin-beams. In this work, we provide a rigorous theoretical description of the spatial properties of bright squeezed light in the presence of strong anisotropy. We investigate a single crystal and a system of two crystals with an air gap (corresponding to a nonlinear SU(1,1) interferometer) and demonstrate the generation of bright correlated twin-beams in such configurations at high gain due to anisotropy. We explore the mode structure of the generated light and show how anisotropy, together with crystal spacing, can be used for radiation shaping.
Keywords: Atomic and Molecular Physics; and Optics

Quantifying the refractive index of ferroelectric domain walls in periodically poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optics Express)
Domain walls (DWs) in ferroelectric (FE) and multiferroic materials possess an ever-growing potential as integrated functional elements, for instance in optoelectronic nanodevices. Mandatory, however, is the profound knowledge of the local-scale electronic and optical properties, especially at DWs that are still incompletely characterized to date. Here, we quantify the refractive index of individual FE DWs in periodically-poled LiNbO 3 (PPLN) single crystals. When applying polarization-sensitive optical coherence tomography (PS-OCT) at 1300 nm using circular light polarization, we are able to probe the relevant electro-optical properties close to and at the DWs, including also their ordinary and extraordinary contributions. When comparing to numerical calculations, we conclude that the DW signals recorded for ordinary and extraordinary polarization stem from an increased refractive index of at least Δn > 2·10 −3 that originates from a tiny region of < 30 nm in width. PS-OCT hence provides an extremely valuable tool to decipher and quantify subtle changes of refractive index profiles for both inorganic and biomedical nanomaterial systems.
Keywords: Atomic and Molecular Physics; and Optics

Integration of Novel Sensors and Machine Learning for Predictive Maintenance in Medium Voltage Switchgear to Enable the Energy and Mobility Revolutions - Hoffmann, Martin W.; Wildermuth, Stephan; Gitzel, Ralf; Boyaci, Aydin; Gebhardt, Jörg; Kaul, Holger; Amihai, Ido; Forg, Bodo; Suriyah, Michael; Leibfried, Thomas; Stich, Volker; Hicking, Jan; et al. (Sensors)
The development of renewable energies and smart mobility has profoundly impacted the future of the distribution grid. An increasing bidirectional energy flow stresses the assets of the distribution grid, especially medium voltage switchgear. This calls for improved maintenance strategies to prevent critical failures. Predictive maintenance, a maintenance strategy relying on current condition data of assets, serves as a guideline. Novel sensors covering thermal, mechanical, and partial discharge aspects of switchgear, enable continuous condition monitoring of some of the most critical assets of the distribution grid. Combined with machine learning algorithms, the demands put on the distribution grid by the energy and mobility revolutions can be handled. In this paper, we review the current state-of-the-art of all aspects of condition monitoring for medium voltage switchgear. Furthermore, we present an approach to develop a predictive maintenance system based on novel sensors and machine learning. We show how the existing medium voltage grid infrastructure can adapt these new needs on an economic scale.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg (Ultramicroscopy)
Keywords: Instrumentation; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Organic Light‐Emitting Diodes Based on a Columnar Liquid‐Crystalline Perylene Emitter - Keum, Changmin; Becker, David; Archer, Emily; Bock, Harald; Kitzerow, Heinz-Siegfried; Gather, Malte C.; Murawski, Caroline (Advanced Optical Materials)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Single-channel electronic readout of a multipixel superconducting nanowire single photon detector - Tiedau, Johannes; Schapeler, Timon; Anant, Vikas; Fedder, Helmut; Silberhorn, Christine; Bartley, Tim (Optics Express)
We present a time-over-threshold readout technique to count the number of activated pixels from an array of superconducting nanowire single photon detectors (SNSPDs). This technique places no additional heatload on the cryostat, and retains the intrinsic count rate of the time-tagger. We demonstrate proof-of-principle operation with respect to a four-pixel device. Furthermore, we show that, given some permissible error threshold, the number of pixels that can be reliably read out scales linearly with the intrinsic signal-to-noise ratio of the individual pixel response.
Keywords: Atomic and Molecular Physics; and Optics

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation. - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)
The characterisation of loss in optical waveguides is essential in understanding the performance of these devices and their limitations. Whilst interferometric-based methods generally provide the best results for low-loss waveguides, they are almost exclusively used to provide characterization in cases where the waveguide is spatially single-mode. Here, we introduce a Fabry-Pérot-based scheme to estimate the losses of a nonlinear (birefringent or quasi-phase matched) waveguide at a wavelength where it is multi-mode. The method involves measuring the generated second harmonic power as the pump wavelength is scanned over the phase matching region. Furthermore, it is shown that this method allows one to infer the losses of different second harmonic spatial modes by scanning the pump field over the separated phase matching spectra. By fitting the measured phase matching spectra from different titanium indiffused lithium niobate waveguides to the model presented in this paper, it is shown that one can estimate the second harmonic losses of a single spatial-mode, at wavelengths where the waveguides are spatially multi-mode.
Keywords: Atomic and Molecular Physics; and Optics

Psychische Auffälligkeiten bei Kindern und Jugendlichen, für die das Jugendamt in Anspruch genommen wurde - Wagenknecht, Inga; Meier-Gräwe, Uta (Praxis der Kinderpsychologie und Kinderpsychiatrie)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics